Mendelian randomization study of lipid species reveals causal relationship with syphilis - Weifeng Shen; Hui Zhou; Wei Wang; Wei Li (AMB Express)
Abstract Although some studies have reported a possible association between lipid and the development and progression of syphilis, the overall causal relationship between lipid and syphilis remains unclear. Data abstracted from extensive genome-wide association studies were utilized to pinpoint genetic variations linked to 179 distinct lipid species. Subsequently, these variations served as instrumental variables in Mendelian Randomization (MR) analyses, aimed at evaluating the causal impact of these lipid species on the occurrence of syphilis. A range of methods, including Weighted Mode, Weighted Median, Simple Mode, MR Egger, and Inverse Variance Weighted, were employed to determine the causal influence. For the purpose of sensitivity analysis, techniques such as Inverse Variance Weighted, MR-Egger, the MR Steiger test, the MR-Egger Intercept Test, and MR-PRESSO were applied. Additionally, Multivariate Mendelian Randomization (MVMR) analyses were conducted to directly assess the causal effect of lipid species on the risk of syphilis. Sterol ester (SE) and phosphatidylcholine (PC) could potentially impact syphilis risk. Specifically, SE (27:1/16:0), SE (27:1/18:2), SE (27:1/18:3), SE (27:1/20:3), and SE (27:1/22:6) were linked to an elevated risk of syphilis. PC (18:2_0:0) was linked to an elevated risk of syphilis. In contrast, PC (16:1_18:0) exhibited a protective role against syphilis. No heterogeneity or horizontal pleiotropy was detected. SE (27:1/16:0), SE (27:1/18:2), SE(27:1/18:3), SE (27:1/20:3), and SE (27:1/22:6) were no longer significantly associated with syphilis in the MVMR analysis (P>0.05). In addition, the previously observed effect of PC (18:2_0:0) on syphilis in univariate MR Was no longer significant in MVMR analysis. However, genetically predicted PC (16:1_18:0) was still significantly negatively associated with syphilis, consistent with univariate MR analysis. We observed that hereditary SE and PC levels appear to be associated with syphilis susceptibility. Future research is needed to understand the mechanisms behind this supposed causation and to develop corresponding treatment strategies.